The Web Won't Be Safe or Secure Until We Break It. - Grossman, Jeremiah (Communications of the ACM, 2013)
The article presents information on security measures in the design of the Internet, with information on personal information security and data collection by websites. Topics include the protection of personally identifiable data, security and data protection services offered by web browsers, and browser attacks by drive-by downloads, which infect the computer's operating system with malware. The Web security industry is discussed, with information on HTML code, security measures for data access control, and the limitations of antivirus software.